Logistics evaluation of an SME as a strategy for its organizational performance - del Ángel-Coronel, Anice (2022)
This research studies a Mexican SME dedicated to manufacturing ecological cleaning and personal care products. A logistics approach allowed us to analyze its supply chain and identify areas of opportunity. The methodology included data collection, supply chain analysis, logistics evaluation, management, review of warehouse logistic indicators, and the SCOR model’s implementation at three process levels (superior, configuration, and elements), each evaluated by key performance indicators. Each indicator was divided into performance attributes (flexibility, assets, speed of service, reliability in compliance, and costs). The DNA Logistik tool was applied to detect the maturity level and risk of logistics operations. As a result, the relevance of five logistics functions in the supply chain (supply, production, storage, transportation, and omnichannel sales) was identified. In addition, the results were compared with 326 records of other SMEs in DNA Logistik in the retail sector.